Glycation of clinically relevant chickpea allergen attenuates its allergic immune response in Balb/c mice. (15th November 2017) - Gupta, Rinkesh Kumar; Raghav, Alok; Sharma, Akanksha; Gupta, Kriti; Neelabh,; Mandal, Payal; Tripathi, Anurag; Ansari, Irfan Ahmad; Das, Mukul; Dwivedi, Premendra D.
Highlights: A chickpea protein (26.1 kDa) belongs to albumin was purified and characterized. This protein has shown its clinical relevance in the terms of IgE affinity. This protein in its native form was found to be allergenic in Balb/c mice. Glycation of this protein causes suppression in its allergic behaviour. Abstract: Glycation of food allergens may alter their immunological behaviour. We sought to investigate the impact of glycation on the allergenicity of a food protein. Herein, a chickpea protein (≈26 kDa) was purified and characterized as lectin. Further, glycation of this purified protein was carried out. Thereafter, allergic behaviour of this glycated protein was compared with its native form, using various allergic parameters in Balb/c mice. The reduced allergenicity of glycated protein was observed as lesser allergic phenotypes, reduced serum immunoglobulins and allergic mediators, lower mast cells and eosinophil counts, lower protein expressions of Th2 cytokines and associated transcription factors. In addition, more Th1 and less Th2 cytokine production in exposed splenocyte, were evident in the glycated protein treated mice as compared to its native protein treatment. Thus, glycation of the chickpea allergen attenuated the sensitizing potential and allergic responses in Balb/c mice significantly and could also be clinically beneficial.